2018
DOI: 10.3390/ijms19010300
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of AQP4 and AQP9 in the Hippocampus Following Eclampsia-Like Seizure

Abstract: Eclampsia is a hypertensive disorder of pregnancy that is defined by the new onset of grand mal seizures on the basis of pre-eclampsia. Until now, the mechanisms underlying eclampsia were poorly understood. Brain edema is considered a leading cause of eclamptic seizures; aquaporins (AQP4 and AQP9), the glial water channel proteins mainly expressed in the nervous system, play an important role in brain edema. We studied AQP4 and AQP9 expression in the hippocampus of pre-eclamptic and eclamptic rats in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Consistent with the present findings, our previous study showed that KA treatment increases the number of AQP4-positive astrocytes in the hippocampus [40]. In another study, AQP4 mRNA and protein levels in the hippocampus were significantly upregulated after eclampsia-like seizures [45]. Ex-4 attenuated all symptoms of BBB leakage, indicating that Ex-4 stabilized KA-induced BBB breakdown.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the present findings, our previous study showed that KA treatment increases the number of AQP4-positive astrocytes in the hippocampus [40]. In another study, AQP4 mRNA and protein levels in the hippocampus were significantly upregulated after eclampsia-like seizures [45]. Ex-4 attenuated all symptoms of BBB leakage, indicating that Ex-4 stabilized KA-induced BBB breakdown.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, an increase in AQP4 in the placenta and fetal membrane from the patient in our study, may be indirect evidence of the increase of AQP4 in the circulation and the brain (27,59). Previous study has found a significant increase in the AQP4 protein in the whole brain during pregnancy in Sprague-Dawley rats (59)(60)(61), suggesting that the increase may be an adaptive adjustment during gestation. However, it has been revealed in rodent experiments that the upregulation of AQP4 in the brain increases the susceptibility of tissues to an autoimmune demyelinating disease attack during and after pregnancy (62).…”
Section: Relationship Between Pregnancy-related Dynamic Immune Changes and Acute Disseminated Encephalomyelitis Pathogenesissupporting
confidence: 60%
“…29 Previous studies demonstrated in preeclamptic placenta an increment of AQP9 expression by Western blot or immunostaining. 15,20,22,26,29 To the best of our knowledge, this is the first study to the current time that has assessed circulating levels of AQP9 in patients with early-onset preeclampsia and compared them with normotensive pregnant women. Also, we included the control and early-onset preeclampsia patient groups that were matched for maternal age, gestational age at blood sample collection, and BMI.…”
Section: Discussionmentioning
confidence: 97%
“…Also, these results might present some evidence towards the brain edema after eclampsia-like seizure and help in the research for treatments for gestational hypertensive disorders. 29 Previous studies demonstrated in preeclamptic placenta an increment of AQP9 expression by Western blot or immunostaining. 15,20,22,26,29 To the best of our knowledge, this is the first study to the current time that has assessed circulating levels of AQP9 in patients with early-onset preeclampsia and compared them with normotensive pregnant women.…”
Section: Discussionmentioning
confidence: 97%